1986
DOI: 10.1073/pnas.83.10.3537
|View full text |Cite|
|
Sign up to set email alerts
|

Growth-associated protein, GAP-43, a polypeptide that is induced when neurons extend axons, is a component of growth cones and corresponds to pp46, a major polypeptide of a subcellular fraction enriched in growth cones.

Abstract: Growth-associated protein, GAP-43, is a polypeptide that is induced in neurons when they grow axons. We show by means of subcellular fractionation and immunohistochemical localization that GAP-43 is a component of neuronal growth cones as well as growing neurites; it is similar to a major phosphoprotein, pp46, of a growth cone-enriched subcellular fraction. These conclusions are consistent with the possibility that the induction of GAP-43/pp46 is an important event in the establishment of a productive growth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
251
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(265 citation statements)
references
References 21 publications
12
251
0
2
Order By: Relevance
“…4A). To confirm this observation, we examined the level of GAP43 in the culture, which serves as the marker of neurite outgrowth 23, and found that GAP43 protein was apparently increased in the NSC‐derived neuron culture by morin hydrate treatment (Fig. 4B).…”
Section: Resultsmentioning
confidence: 71%
“…4A). To confirm this observation, we examined the level of GAP43 in the culture, which serves as the marker of neurite outgrowth 23, and found that GAP43 protein was apparently increased in the NSC‐derived neuron culture by morin hydrate treatment (Fig. 4B).…”
Section: Resultsmentioning
confidence: 71%
“…Developmentally, RGCs express this protein during axon outgrowth and synaptic refinement, then downregulate it as their connections mature (Skene and Willard, 1981b;Meiri et al, 1986;Moya et al, 1988). Normally, GAP-43 is transiently upregulated after axotomy and declines as RGCs undergo atrophic changes (Doster et al, 1991;Fournier et al, 1997;Wodarczyk et al, 1997;Wouters et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Because RGCs only express GAP-43 during axon outgrowth, probes for this protein enable one to visualize RGCs in a growth state (Meiri et al, 1986;Moya et al, 1988;Doster et al, 1991;Schaden et al, 1994;Berry et al, 1996). In animals having a nerve crush combined with lens puncture, numerous GAP-43-positive axons grew past the injury into the distal optic nerve (Fig.…”
Section: Axon Outgrowthmentioning
confidence: 99%
“…We next analyzed the morphology of axon terminals of olfactory neurons during synaptogenesis using GAP43-EGFP as a marker, because GAP43 is enriched in the plasma membrane of axonal growth cones (Meiri et al, 1986;Skene, 1989), and GAP43-EGFP fusion protein was targeted to the growth cone (Nakata et al, 1998). We injected the omp promoter-driven GAP43-EGFP construct (Fig.…”
Section: Axon Terminal Morphology Of Olfactory Sensory Neurons Duringmentioning
confidence: 99%